(untitled) (Alternautas, 2022)
The quality and trends of the policymaking processes in Latin America have been under permanent debate. A rich literature has pointed out different factors that have influenced policymaking since the return to democracy in the 1980s. Particularly important objects of debate have been the political and ideological predominant positions, like the neoliberal (1980s-1990s) and pink (2000s-2010s) waves (Castañeda, 2006; Roberts, 2007; Levistky and Roberts, 2011; Kingstone, 2011). It has also been pointed out the influence of the economic trends that the region has faced, and the internal economic imbalances that produced crisis and adjustments (Ffrench-Davis, 2000; Diez and Franschet, 2012; Haggard and Kaufman, 2012). Other issues discussed are more politically structural, like the balance of power under presidential regimes, how the structure of policymaking is set up between Government and Parliament or under Unitarian/Federal regimes, and the structure of political participation and the composition (fragmented/majoritarian) of political coalitions in Government or Parliament (Stein et al., 2008; Aninat et al. 2008; Sehnbruch and Siavelis, 2014). Finally, the debate also highlighted the importance of different stakeholders (i.e. business elites) and their influence in Latin American policymaking (Cook, 2007; Schneider, 2008; Karcher and Schneider, 2012). The overlapping of these issues are key to understand how policies evolve. However, even though general economic, political and societal waves define a trend or direction, the differences in terms of magnitude and sustainability of policies among countries show there are idiosyncratic elements for explaining changes.